Performance of different weighting and surface fitting techniques on station-wise TEC calculation and modified sine weighting supported by the sun effect. Issue 2 (4th May 2019) - Şentürk, Erman; Çepni, Murat Selim
Abstract: The total electron content (TEC) is a significant parameter to describe the current electron density of the ionosphere in GNSS studies. The slant total electron content (sTEC) is computed from the signal delay along the signal path from observations to GNSS satellites in view at any epoch and it can be converted to the vertical total electron content (vTEC) by a mapping function. The station-wise TEC is generally calculated by the simple weighted average of the vTEC values or surface interpolation techniques. In this study, two different weighting algorithms and three different surface interpolation techniques were used in three IGS stations located at different zones on the most disturbed and quietest days in 2014. Calculated TEC values were compared with the GIM-vTEC (IGS) global model. In addition, a new weighting algorithm was investigated and it is defined as modified sine weighting supported by the local solar effect. Results show that a linear or natural break technique in surface interpolation provides more accuracy.